Heterojunctions between amorphous and crystalline niobium oxide with enhanced photoactivity for selective aerobic oxidation of benzylamine to imine under visible light1. Issue 35 (21st September 2015) - Zhang, Yantao; Pei, Linjuan; Zheng, Zhanfeng; Yuan, Yong; Xie, Tengfeng; Yang, Juan; Chen, Shuai; Wang, Junwen; Waclawik, Eric R.; Zhu, Huaiyong
<x xml:space="preserve">Abstract</x> Nb2O5 microfibres with heterojunctions between amorphous and crystalline phases show improved photocatalytic activity in Nb2O5–benzylamine surface complex photocatalytic process.